Implementasi Kurikulum Merdeka Pada Madrasah Ibtidaiyah di Indonesia - Idris, Syarifuddin; Adawiah, Rabiatul (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
Ibtidaiyah have been carried out. However, there has been no survey of articles related to research on the implementation of the independent curriculum at Madrasah Ibtidaiyah in Indonesia. Thus, this research aims to classify all the research relate to research on the implementation of the independent curriculum at Madrasah Ibtidaiyah in Indonesia. Systematic Literature Review (SLR) method which is used to identify research result on the topic. These research data come from 9 articles of 9 which have been accredited by the Ministry of Research, Technology of Higher Education of the Republic of Indonesia in the Sinta 3, 4, and 5 categories. The result of the research mapped all the articles analysed into five categories namely; subject, class, student ability, and method used in the research. The result of this research exposed information related to research on the implementation of the independent curriculum at Madrasah Ibtidaiyah in Indonesia. Then research could became recommendation for further research on the implementation of the independent curriculum at Madrasah Ibtidaiyah in Indonesia Keywords: independent curriculum, madrasah ibtidaiyah, journals accredited in level 3, 4, and 5, systematic literature review.